Effects of moisture and redox reactions in VCM and ECM resistive switching memories. (21st August 2018) - Valov, Ilia; Tsuruoka, Tohru
Abstract: Redox-based memristive devices (ReRAM) have been intensively studied in recent years with respect to their functions as applications in non-volatile memories, selector devices and building units for beyond von Neumann computing. Despite the fact that many details regarding the switching mechanism have been reported and that significant improvements in the device performance have been achieved, the large variability remains a serious disturbing factor. One of the sources of this variability was shown to be moisture. It can be absorbed from the local environment or during device fabrication. The role of the water molecules is multifold—a source for a counter electrode reaction, they provide additional charges in the oxide matrix, i.e. protons or oxygen, they enhance the ion diffusion and act as a corrosive agent. In this review, we discuss how moisture is incorporated in oxides and its impact on the ReRAM device operation. We show that it affects not only the electrochemical redox characteristics, but that it also increases the conductivity of the material and modulates the switching kinetics. The particular influence of H2 O for both electrochemical metallization memories (ECM) and valence change memories (VCM) is exemplarily demonstrated and discussed. The importance of controlled moisture content as a component in the ReRAM devices as a memory and neuromorphic units is highlighted.